Letter to Jane Tolmach from Charles Warren - Charles Warren:::::: (1968)
This January 31, 1968 letter from Charles Warren of the California Democratic Presidential Delegation Committee informs Jane Tolmach that the process of selecting delegates to the Democratic National Convention is underway. A staff in San Francisco is gathering names for consideration by the Selection Committee, which is scheduled to meet around February 17 to make final decisions. Tolmach is asked to submit additional delegate recommendations using enclosed forms and to provide background information and contact details for each nominee. The letter explains that each congressional district may select four delegates, with twenty additional delegates chosen at large, and notes updated district boundaries. It also reminds her that the estimated cost for each delegate to attend the convention will be approximately $750.